Elucidating the neuromeric organization of the Mongolian gerbil brain - F. Lucero-Arteaga; S. Labegorra; A. Abrego-Alvarez; V. Heck; A. I. Portu; M. A. Boeris; A. Alonso; B. Ribeiro Do-Couto; M. Á. García-Cabezas; K. Y. Tseng; José Luis Ferran (Brain Structure and Function, 2025)
The Mongolian Gerbil ( Meriones unguiculatus ) diverged from rats/mice around 45 million years ago and developed adaptations to extreme temperatures and water scarcity. Another feature of the Mongolian Gerbils is their social monogamy similar to that of prairie voles. These observations suggest that there are potential differences in the Mongolian Gerbil brain that are distinct from that of rats and mice. The goal of the present study is to establish the extent to which the neuromeric organization of the brain is conserved in the Mongolian Gerbil and to gain insights on how evolutionary expansion and diversification of brain regions occur across species. Our data shows that the multineuromeric origin of tyrosine hydroxylase-positive processes in the Mongolian Gerbil is similar to that in mice and rats, spanning from the diencephalon, midbrain, and the rostral hindbrain. There are also observable anatomical differences. However, most of the components characteristic of these neuromeres are identifiable in the Mongolian gerbil, closely mirroring those found in mice and rats. Together, these findings suggest that the conserved neuromeric organization likely stems from a restricted genetic toolset that began in the Muridae family 45 million years ago, and that a profound reorganization of the fundamental structural plan delineating the neuromeric segmentation is not required for the emergence of diverse functionality among species of phylogenetically related families. Future studies are needed to establish how the genetic programs within each neuromeric unit are influenced by environmental factors that ultimately impact the size of the neuromeric derivatives and their functional connectivity.